2017
DOI: 10.1177/0046958017711759
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With Electronic Medical Records Privacy Policy: An Empirical Investigation of Hospital Information Technology Staff

Abstract: The employment of Electronic Medical Records is expected to better enhance health care quality and to relieve increased financial pressure. Electronic Medical Records are, however, potentially vulnerable to security breaches that may result in a rise of patients’ privacy concerns. The purpose of our study was to explore the factors that motivate hospital information technology staff’s compliance with Electronic Medical Records privacy policy from the theoretical lenses of protection motivation theory and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Through compliance with a stated privacy policy, employees of these healthcare facilities can effectively protect the privacy of the patients. Despite several studies which have investigated the determinants of adherence to a privacy policy [4, 5, 8, 11, 58], patient privacy and the ultimate success of EMR remain dependent on continuance protection rather than on one time protection. Surprisingly, prior to this particular study, little, if any, effort has been made to fill this gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through compliance with a stated privacy policy, employees of these healthcare facilities can effectively protect the privacy of the patients. Despite several studies which have investigated the determinants of adherence to a privacy policy [4, 5, 8, 11, 58], patient privacy and the ultimate success of EMR remain dependent on continuance protection rather than on one time protection. Surprisingly, prior to this particular study, little, if any, effort has been made to fill this gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Via EMR, healthcare professionals can serve to inquire after patient information immediately without the limitations of time and space [3]. However, with the advent of a more accessible and comprehensive EMR system, a massive amount of medical records may become easily obtainable to both unauthorized and authorized users who are both inside and outside the healthcare facilities [4]. EMR are therefore potentially susceptible to security breaches which may lead to real patients’ privacy concerns [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMT postulates that threats and coping appraisal motivate an individual to undertake self-protective behavior [25]. The PMT model has been applied to examine health-related intention and behavior, for example, the way to change attitude in embracing healthier living [36], the adoption of mobile health services [26,37], and compliance with electronic medical record privacy policies [38]. Babazadeh et al [36] conducted a study to explore the factors that shaped skin cancer preventive behaviors (SCPB) in rural areas and suggested that it was the perceived susceptibility that influenced preventive behaviors among farmers.…”
Section: Methodsmentioning
confidence: 99%
“…The study of the behaviour of documentation from auxiliary sources in the current practice of medical staff has received little attention so far. Most papers refer to the implementation of medical data recording systems in hospitals (Bae et al, 2017;Sher et al, 2017;Damotte et Jindal & Raziuddin, 2018) and do not focus on the constant need to inform the medical staff in order to be up to date with the latest research, carried out at international level. The few published articles addressing the importance of information from accredited online sources present case studies covering a limited number of countries (Hider et al, 2009;Lindsey & Olin, 2013), such as: Mongolia (Callen, Buyankhishig & McIntosh, 2008), Saudi Arabia (Khudair & Cooke, 2008), Australia (Rowlands, Coverdale, & Callen, 2016;Shepheard, 2017) or Nigeria (Watts & Ibegbulam, 2006).…”
Section: Introductionmentioning
confidence: 99%